2010
DOI: 10.3340/jkns.2010.47.5.370
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SpineJet™ XL and Conventional Instrumentation for Disk Space Preparation in Unilateral Transforaminal Lumbar Interbody Fusion

Abstract: Objective : Although unilateral transforaminal lumbar interbody fusion (TLIF) is widely used because of its benefits, it does have some technical limitations. Removal of disk material and endplate cartilage is difficult, but essential, for proper fusion in unilateral surgery, leading to debate regarding the surgery's limitations in removing the disk material on the contralateral side. Therefore, authors have conducted a randomized, comparative cadaver study in order to evaluate the efficiency of the surgery wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
1
9
0
3
Order By: Relevance
“…4 However, in vitro studies have shown that discectomy is not always ideal in terms of maximizing the CSA and preparing the endplate. 3,7 In this study, the CSA of the discectomy ranged from 38% to 48% depending upon technique, and this was similar to the overall discectomy areas of the previously mentioned studies. The current study also confirmed, quantitatively, the difficulty of removal of material from the posterior-contralateral region for a TLIF procedure.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…4 However, in vitro studies have shown that discectomy is not always ideal in terms of maximizing the CSA and preparing the endplate. 3,7 In this study, the CSA of the discectomy ranged from 38% to 48% depending upon technique, and this was similar to the overall discectomy areas of the previously mentioned studies. The current study also confirmed, quantitatively, the difficulty of removal of material from the posterior-contralateral region for a TLIF procedure.…”
Section: Discussionsupporting
confidence: 86%
“…
T ransforaminal lumbar interbody fusion (TLIF) is arguably the most widely used approach for lumbar interbody arthrodesis. 3,7 It was initially described by Harms in the early 1980s. 1,2 The TLIF method has become popular for achieving interbody fusion, in part by limiting the need for a second anterior approach and avoiding the risks associated with anterior lumbar surgery.There are concerns, however, about the amount of disc material that can be removed posteriorly.
…”
mentioning
confidence: 99%
“…Ablasyon için suyun yüksek yoğunluktaki akımına bir odaklanmayla kullanılır, aynı zamanda dokuyu aspire eder (12) . Kadavraları kullanan bir çalışmada, kusursuz bir prosedür olarak hızlı bir şekilde uygulanmıştır (30) . Biz çalışmamızı canlı hasta grubunda uyguladık.…”
Section: Sinir Sistemi Cerrahisi / Cilt 5 / Sayı 1-2 2015unclassified
“…The technique is used clinically for cutting soft tissues like liver tissue [3][4][5][6] and experimentally for dissecting spleen tissue [7,8], kidney tissue [9][10][11][12] and brain tissue [2,13,14]. Waterjets have also been investigated for cutting hard materials such as bone and bone cement [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%